Oral Health Related Knowledge And Attitude Of Anganwadi of Mangalore City, India - Shakya, Ajay; Rao, A; Shenoy, R; Shrestha, M (Journal of Chitwan Medical College, 2014)
Dental caries is a common childhood disease. Its prevalence can be reduced by integrating dental strategies into primary health care approach. Knowledge, attitude and practice of anganwadi workers in the subject of oral health is imperative in achieving this goal. This study was therefore conducted to assess the knowledge and attitude towards oral health among anganwadi workers of Mangalore city. A questionnaire study, using convenience samples was conducted among 159 anganwadi workers of Mangalore city. A close ended questionnaire consisting of 20 questions was used. Details of age and qualification were recorded. The data was analyzed using SPSS 11.5. Only 45.9% of the anganwadi workers knew that dental caries was a disease, 57.2% knew that the best time to eat sweets was during meal time, 58.5% workers stated dentists as their source of oral health information. Almost all of the Anganwadi workers were positive towards the importance of oral health education and expressed their willingness to teach children how to brush properly and obliged to advise a child needing dental care to go to dentist. An anganwadi worker can be a vital link in the health care delivery system. There is a need to educate them on oral health in order to reach children at an early and receptive age. It is very important on the part of the health department to carry out effective programmes on oral health for anganwadi workers. Journal of Chitwan Medical College 2013; 3(4); 6-8 DOI: http://dx.doi.org/10.3126/jcmc.v3i4.9545